FRAUD HEXAGON THEORY AND FRAUDULENT FINANCIAL STATEMENTS IN BASIC INDUSTRIAL AND CHEMICAL SECTOR COMPANIES LISTED ON THE IDX - Rozi, M Mufti Fahrul; Munari, Munari (Yayasan Education and Social Center, 2024)
Financial statement fraud (FSF) is the act of reporting inaccurate or distorted financial information to manipulate company performance or gain illegitimate personal gain. This research examines the influence of elements in the Hexagon Fraud on financial statement fraud. The analytical method used in this research is multiple linear analysis using purposive sampling technique to select the research sample. The sample for this research was 19 companies in the basic industrial and chemical sectors listed on the IDX from 2021 to 2022 with a 2-year observation period, totaling 38 sample companies. The results obtained are as follows: (X1) Financial stability as an element of Stimulus measurement in the fraud hexagon theory, (X2) frequent number of CEO Picture as an element of Ego measurement in the fraud hexagon theory, (X3) Change in auditor as an element of Rationalization measurement in the hexagon fraud theory, (X4) nature of industry as an element of Opportunity measurement in the hexagon fraud theory, (X5) change of directors as an element of Capability measurement in the fraud hexagon theory, and (X6) government projects as elements of Collusion measurement in the hexagon fraud theory. Simultaneously, they influence fraud in financial statements, while Stimulus, Ego, Rationalization, and Opportunity have no influence on financial statements. Capability and Collusion influence financial statement fraud